Correspondence between classification systems in information retrieval systems of libraries - Halytska, Svitlana (Bìblìotečnij vìsnik, 2023)
The purpose of the study is to substantiate the feasibility of using different subjectization and classification systems during the scientific processing of documents, indication in unified bibliographic records of independent classifiers, as well as to clarify the importance of different information retrieval languages and their correspondence to ensure thematic search in electronic library. The research methodology is based on the use of general scientific and special research methods (generalization, systematic, classification, descriptive). Scientific novelty. The article considers the issue of application of different subjectization and classification systems during the scientific processing of documents and indication in unified bibliographic records of documents of independent classifiers. It is noted that modern libraries use different systems of knowledge organization and supplement bibliographic records with subject-oriented data, which creates additional unified points of access to information resources. The expediency of using different information retrieval languages in thematic search in the electronic catalog of a modern library is substantiated. Conclusions. It was found that the indication in the bibliographic records of the correspondence between the components of the linguistic support of search engines of different libraries creates additional points of access to information, determines the versatility and efficiency of information systems. It is proved that it is important to indicate classification indexes and thematic headings in bibliographic records of documents, which allows the user to limit the search to a certain thematic area. The importance of moving to related headings or codes / indexes of different classifications by hyperlinks is emphasized, which allows the user to access more sources of information. It was found that the consistency of different national lists of subject headings and classification hierarchies is aimed at creating conditions for joint use of library funds, interlibrary exchange of information, contributes to a complete and relevant result of in-depth thematic search.